Identification of Camellia oleifera WRKY transcription factor genes and functional characterization of CoWRKY78 - Li, Jingbin; Xiong, Chaowei; Ruan, Dong; Du, Wei; Li, He; Ruan, Chengjiang (Frontiers in Plant Science, 2023)
Camellia oleifera Abel is a highly valued woody edible oil tree, which is endemic to China. It has great economic value because C. oleifera seed oil contains a high proportion of polyunsaturated fatty acid. C. oleifera anthracnose caused by Colletotrichum fructicola, poses a serious threat to C. oleifera growth and yield and causes the benefit of the C. oleifera industry to suffer directly. The WRKY transcription factor family members have been widely characterized as vital regulators in plant response to pathogen infection. Until now, the number, type and biological function of C. oleifera WRKY genes are remains unknown. Here, we identified 90 C. oleifera WRKY members, which were distributed across 15 chromosomes. C. oleifera WRKY gene expansion was mainly attributed to segmental duplication. We performed transcriptomic analyses to verify the expression patterns of CoWRKYs between anthracnose-resistant and -susceptible cultivars of C. oleifera. These results demonstrated that multiple candidate CoWRKYs can be induced by anthracnose and provide useful clues for their functional studies. CoWRKY78, an anthracnose-induced WRKY gene, was isolated from C. oleifera. It was significantly down-regulated in anthracnose-resistant cultivars. Overexpression of CoWRKY78 in tobacco markedly reduced resistance to anthracnose than WT plants, as evidenced by more cell death, higher malonaldehyde content and reactive oxygen species (ROS), but lower activities of superoxide dismutase (SOD), peroxidase (POD), as well as phenylalanine ammonia-lyase (PAL). Furthermore, the expression of multiple stress-related genes, which are associated with ROS-homeostasis (NtSOD and NtPOD), pathogen challenge (NtPAL), and pathogen defense (NtPR1, NtNPR1, and NtPDF1.2) were altered in the CoWRKY78-overexpressing plants. These findings increase our understanding of the CoWRKY genes and lay the foundation for the exploration of anthracnose resistance mechanisms and expedite the breeding of anthracnose-resistant C. oleifera cultivars.